Hakikat Manusia ( Perspektif Filsafat Pendidikan Islam) - Vina Destiana; lntan Putri Lestari; M Haris Hanafi; M Sofwan Ghalib; Wismanto Wismanto (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This article aims to describe human nature from the perspective of Islamic educational philosophy in order to gain a comprehensive understanding of human nature. The main sources for this type of qualitative research, called library research, are books, journals and other scientific articles. The collected data was analyzed using content analysis to make it easier for the author to filter the main ideas from various existing sources and narrate them as the focus of the research. The results of this article's research: (1) The terms used to refer to humans in the Koran include al-Insan (refers to humans who have special qualities and potential), al-Basyar (refers to humans as living creatures), and al-Insan (calls humans who have privileges and humans who have potential), al-Basyar (calls humans as living creatures). -Nas (calls humans as social creatures): (2) Characters have different views but are essentially the same regarding the nature of humans, namely humans are creations whose potential is different from other creations of God: (3) Humans are called ahsan al-taqwin , which places humans in a strategic position as servants of Allah and Caliph of Allah. Therefore, humans should try to discover their true nature to realize how great a gift God has given in the form of potential so that humans can optimally carry out their functions in worship and serve Allah SWT.